Jumpstarting Orange- Fleshed Sweetpotato in West Africa through Diversified Markets - International Potato Center (2016)
In the third year of the project, pilot efforts to develop markets for orange fleshed sweetpotato to generate income and help combat vitamin A deficiency, are accelerating in Ghana, Nigeria and Burkina Faso.